Dynamics of coastal weather effects on Moler disease in Indonesia shallot production - Cornelin Abolla, Natasha Belandina; Sartohadi, Junun; Setiawan, Muhammad Anggri (Agriculture and Natural Resources, 2025)
Importance of the work: Coastal microclimatic factors influence pathogen dynamics; however, their impact on shallot diseases, such as Moler disease, remains poorly understood. Objectives: To investigate multivariate relationships between coastal weather parameters and Moler disease development in shallot production systems. Materials and Methods: Field surveys were conducted across 15 sites in Parangtritis, Yogyakarta, Indonesia, during the late rainy and dry seasons. Disease incidence and infection rates were assessed weekly alongside six weather parameters monitored via an automatic weather station. Principal component analysis (PCA) was used to analyze weather-disease relationships. Results: Disease incidence was significantly higher during late rainy season (28.50%) compared to dry season (12.03%, p = 0.03), with infection rates of 0.14 units/d and 0.09 units/d (p < 0.001). The PCA revealed 84.62% of the weather-diseases relationship variance was explained by the two principal components. Radiation-precipitation variables had strong positive associations with infection rates, while relative humidity had an unexpected negative correlation (Pearson’s correlation coefficient r = -0.55). Temperature had a secondary influence through weak through positive F2 loadings (25.54%, r = 0.25). Main finding: Coastal weather-disease interactions deviated from inland patterns, particularly in humidity-disease relationships, necessitating maritime-specific disease prediction models for effective management.